2022
DOI: 10.1002/adma.202107901
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Stretchable Superamphiphobic Surfaces with Deformation‐Induced Rearrangeable Structures

Abstract: we now profit from an improved understanding of the mechanisms of a superamphiphobic surface, a less complex method of preparation and a high mechanical stability of the surface are still two of the main challenges that have hindered its widespread adoption. [7] Recently, superliquid-repellent surfaces with deformation-resistant performance are becoming increasingly significant in various situations such as flexible electronics, [8] artificial skin, [9] textile dressings, [10] and liquid manipulation. [11]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…
and thermal properties of engineered surfaces to impart multifunctions in complex operating environments including varying temperature and humidity is critical. Of special interest is natural superhydrophobic surfaces found on the skins of many living organisms, [2][3][4][5][6] and bioinspired artificial coatings widely adopted in energy-related processes such as self-cleaning, [7][8][9] thermal management, [10][11][12] energy harvesting, [13][14][15] droplet manipulation, [16,17] antifogging, [18,19] anti-biofouling, [20] and anti-icing. [21][22][23] In spite of extensive progress, practical implementations of superhydrophobic coatings with preferred functionalities and durability for energy saving dictate a wide-spectrum robustness including mechanochemical strength, high adhesion with substrates, and flame resistance, a challenge remaining unsolved to date.However, it appears difficult to mutually achieve all these features in one design.
…”
mentioning
confidence: 99%
“…
and thermal properties of engineered surfaces to impart multifunctions in complex operating environments including varying temperature and humidity is critical. Of special interest is natural superhydrophobic surfaces found on the skins of many living organisms, [2][3][4][5][6] and bioinspired artificial coatings widely adopted in energy-related processes such as self-cleaning, [7][8][9] thermal management, [10][11][12] energy harvesting, [13][14][15] droplet manipulation, [16,17] antifogging, [18,19] anti-biofouling, [20] and anti-icing. [21][22][23] In spite of extensive progress, practical implementations of superhydrophobic coatings with preferred functionalities and durability for energy saving dictate a wide-spectrum robustness including mechanochemical strength, high adhesion with substrates, and flame resistance, a challenge remaining unsolved to date.However, it appears difficult to mutually achieve all these features in one design.
…”
mentioning
confidence: 99%
“…It was shown that by increasing the silane loading, although the transparency of the surface decreased, the WCA increased. In another study, Zhou et al [ 48 ] first spray-coated PDMS (as the binding layer) and then a solution of silicone nanofilaments (NF) in toluene on a pre-stretched substrate (a commercial cis-1,4-polyisoprene tape), followed by curing the surface at 80 °C for 2 h, and fluorination by chemical vapor deposition ( Figure 10 ). The NFs formed dense re-entrant nano- and micro-scale structures that showed repellency against water and oil (n-hexadecane) for at least one thousand stretch-release cycles, resulting in a durable stretchable superamphiphobic surface.…”
Section: Micro- and Nanofabrication Techniques To Create Superhydroph...mentioning
confidence: 99%
“…Scale bar = 200 μm; ( c ) SEM images of the NFSS surface at various magnifications. Scale bar = 50 μm ( top ), 2 μm ( bottom ), and 500 nm (inset); and ( d ) schematic illustration of microstructures on the NFSS after releasing the surface from the stretched state (Reproduced from [ 48 ] with permission from John Wiley and Sons).…”
Section: Figurementioning
confidence: 99%
“…One-dimensional nanoparticles can exhibit nanorod ( Selim et al, 2019 ; Selim et al, 2022a ; Selim et al, 2022b ), nanowire ( Zhang et al, 2013 ; Li et al, 2020 ), nanofilament ( Zhou et al, 2022 ), nanotube ( Wang et al, 2010 ), and nanofiber structures ( Chen et al, 2009 ; Liang et al, 2020 ), among other morphologies. Mohamed S. Selim et al fabricated a superhydrophobic nanocoating based on PDMS and ZnO nanorods; the coating exhibited long-term antifouling abilities for marine applications ( Selim et al, 2019 ).…”
Section: Superhydrophobicity Based On Polydimethylsiloxane With Nanop...mentioning
confidence: 99%